Changes in corneal scleral rigidity and corneal thickness at various target intraocular pressures in patients with stabilized primary open-angle glaucoma (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Current methods for determining target IOP have disadvantages. Investigation of data on corneoscleral rigidity and corneal thickness in patients with stabilized primary open-angle glaucoma of stages I-II may improve the method of determining target IOP.Purpose. To study the correlation between indices of corneoscleral rigidity, corneal thickness and target IOP in patients with stabilized primary open-angle glaucoma  (POAG) of stages I-II.Material and Methods. 30 patients (30 eyes) with stabilized POAG of the І-ІІ stage were examined. The patients underwent pachymetry, applanation tonometry, dynamic contour tonometry, corneal rigidity determination and tonography. The progression of glaucoma was monitored by the HFA II Central 30-2 Threshold Test and SOCT Copernicus + units. Target IOP was calculated taking into account the age and the level of diastolic blood pressure.Results. It was found that, in group 1 with target IOP of 6.2 -13.9 mm Hg, the corneal thickness was 540-590 μm and rigidity of the cornea ranged from 1.0 to 4.0 mm Hg; while in group 2 with target IOP of 14.0 -16.8 mm Hg, the corneal thickness was 510-570 μm and rigidity of the cornea ranged from -3.0 to 1.5 mm Hg.Conclusions. It was found that the lower a value of achieved target IOP, the higher corneal rigidity in patients with stabilized stage I-II POAG.
Keywords: target intraocular pressure; primary open-angle glaucoma; corneal thickness; corneal rigidity